The conduit-seal system of hypogene karst in Neoproterozoic carbonates in northeastern Brazil. (March 2019) - Cazarin, Caroline L.; Bezerra, Francisco H.R.; Borghi, Leonardo; Santos, Roberto V.; Favoreto, Julia; Brod, José A.; Auler, Augusto S.; Srivastava, Narendra K.
Abstract: Karst processes are of primary importance for the generation of secondary porosity and permeability in carbonate reservoirs and aquifers. The topic investigated in this study are the effects of the facies and stratigraphy of different layers on the vertical distribution of solution cavities formed by hypogenic fluids in a carbonate sequence. This work uses the Toca da Boa Vista (TBV) and Toca da Barriguda (TBR) caves as analogues of carbonate reservoirs that are affected by karst processes. These are two different caves that are 400 m apart but exhibit the same geological characteristics and occur in the Neoproterozoic Salitre Formation (700-560 Ma), São Francisco Craton, Brazil. These caves form the longest cave system in South America, with conduits of lengths ∼107 km (TBV) and ∼34 km (TBR). Previous studies of these caves indicated their hypogene origins. These caves developed by an ascending fluid flow, mainly along fractures. The fluid then flowed laterally and was influenced by the following five stratigraphic units, from the bottom to the top: (1) cross-bedded oolitic grainstone, (2) fine grainstone with chert nodules, (3) microbial carbonate, (4) interbedded fine siliciclastics and marls, and (5) crystalline grainstone interfingered with chert layers. Units 4 and 5 formed a stratigraphic seal. Units 1, 2, and 3 below the seal supported the lateral redistribution of flow and respective conduit development. Therefore, these units exhibit a high degree of karstification. Veins related to the first fluid phases that compose a hydrothermal mineral assemblage cut across these units. We conclude that stratigraphic control is important for determining the architecture of the hypogenic cave system at the local scale. Highlights: We study the lithostratigraphy and vein mineralogy of giant hypogenic caves. Vein hypogene infillings include a hydrothermal assemblage of minerals. The caves comprise a conduit-seal system in the carbonate-siliciclastic unit. Lateral flow followed the dissolution of ascending fluids through vertical fractures. Local stratigraphy controls the horizontal dissolution and karst development.